The Honest Enterprise Research Broker: Facilitating Ethical, Efficient, and Secure Access to Health Data for Research - Keller, Michelle S.; Roberts, Pamela; Japardi, Kevin; Ebinger, Joseph E.; Davis, Tod; Pevnick, Joshua; Chevvuri, Sivathmika; Stuck, Hudson; Huang, Shao-Chi; Kowalewski, Edward; Lin, Ashley; Sanapanya, Andrew; Tomines, Alan; SooHoo, Spencer (Applied Clinical Informatics, 2025)
Background Health systems generate and store vast amounts of clinical data, requiring structured processes to ensure that secondary use of the data is available to researchers in an efficient, ethical, and secure manner.Objective We describe a process to provide data to health system researchers at a large, multi-hospital health system that balances efficiency with security and ethics.Methods The Honest Enterprise Research Broker (HERB) Committee has enacted a systematic process to deliver investigators requesting data, using pre-written SQL code, when possible, to increase efficiency, providing a suite of self-service tools for cohort size estimation, and assessing the security and privacy of data leaving the institution. We evaluated the number of extracts per year, the average time to delivery of the data extract, and user satisfaction with the process.Results From 2018 to 2023, the HERB Committee completed 487 data extracts. The number of requests increased from 51 in 2018 to 121 in 2023. Even as the number of extracts increased, the number of hours per extract decreased from 12.5 in 2018 to 9 in 2023. User satisfaction surveys found a high degree of satisfaction with the process.Conclusion Through a process of continuous improvement, the HERB Committee has developed an expedient process to support the research needs of a large academic multi-hospital health system.
Keywords: clinical data access; health system; honest broker